A transcendência de PI, E e dos Números de Liouville - Oliveira, Josivaldo Reis (2015)
In this dissertation subtly discuss some historical facts in relation to the number and number of Euler and some basics on the sets of rational numbers and reais. We will also show some numbers algebraic and transcendental, as well as their enumerabilidades, the rst transcendental number and nally the demonstration of the transcendence of Liouville numbers, Euler and .